Multiple Independent Retroelement Insertions in the Promoter of a Stress Response Gene Have Variable Molecular and Functional Effects in Drosophila. - Miriam Merenciano; Anna Ullastres; M A R de Cara; Maite G Barrón; Josefa González (PLoS Genetics)
Promoters are structurally and functionally diverse gene regulatory regions. The presence or absence of sequence motifs and the spacing between the motifs defines the properties of promoters. Recent alternative promoter usage analyses in Drosophila melanogaster revealed that transposable elements significantly contribute to promote diversity. In this work, we analyzed in detail one of the transposable element insertions, named FBti0019985, that has been co-opted to drive expression of CG18446, a candidate stress response gene. We analyzed strains from different natural populations and we found that besides FBti0019985, there are another eight independent transposable elements inserted in the proximal promoter region of CG18446. All nine insertions are solo-LTRs that belong to the roo family. We analyzed the sequence of the nine roo insertions and we investigated whether the different insertions were functionally equivalent by performing 5'-RACE, gene expression, and cold-stress survival experiments. We found that different insertions have different molecular and functional consequences. The exact position where the transposable elements are inserted matters, as they all showed highly conserved sequences but only two of the analyzed insertions provided alternative transcription start sites, and only the FBti0019985 insertion consistently affects CG18446 expression. The phenotypic consequences of the different insertions also vary: only FBti0019985 was associated with cold-stress tolerance. Interestingly, the only previous report of transposable elements inserting repeatedly and independently in a promoter region in D. melanogaster, were also located upstream of a stress response gene. Our results suggest that functional validation of individual structural variants is needed to resolve the complexity of insertion clusters.